Temperature Gradient ZnO Deposited via ALD for High-Performance Transistor Applications - Bowen Che (IEEE, 2020)
This work reports an alternative atomic layer deposition (ALD) method to fabricate ZnO thin-film transistors (TFTs). The ZnO film is deposited with temperature naturally-cooling process from 200 to 100°C, called a “temperature gradient ZnO (TG-ZnO)”). After optimized annealing treatment at 300°C, the TG-ZnO TFT shows an excellent performance compared to those fabricated with traditional constant temperature deposition, including a high saturation mobility $\left(μ_{\text {sat }}\right)$ of 11.8 cm2/Vs, which is 5 times higher than the ZnO TFT, a good on/off-state current ratio $\left(I_{on} / I_{off}\right)$ of $1.9 × 10^{7}$ , a small subthreshold swing ( $SS$ ) of 175 mV/decade and a threshold voltage $\left(V_{th}\right)$ of 1.1 V. Meanwhile, the TG-ZnO TFT has better crystallization than 100°C-ZnO and lower oxygen vacancies than 200°C-ZnO. These characters enable the TG-ZnO TFT not only to maintain a high mobility, but also to present a satisfactory $I_{on} / I_{off}$ ratio. This promising deposition technique provides a new idea for fabricating TFTs with high mobility.